Green Synthesis, Characterization of Copper Sulfide Nanoparticles and Antibacterial Activity Evaluation - Lafta, Kawther Thamer; Salman, Taghried Ali (Iraqi Journal of Science, 2024)
This study focused on the eco-friendly and economical synthesis of copper sulfide nanoparticles at certain temperatures using myrtle leaf extract. Green synthesis methods are mostly considered to be safe and efficient in the nanoparticle synthesis field. The nanoparticles were characterized using FT-IR, AFM, UV-visible spectrophotometer, FESEM with EDX, and XRD. where the crystal size in XRD was 21.4 nm. The antibacterial properties of CuS nanoparticles were evaluated against two bacterial strains, namely, Staphylococcus aureus and Escherichia coli, using various concentrations. The Minimum Inhibitory Concentration (MIC) was determined for both bacteria at a range of CuS NPs conc. from 0.5229 × 10-1 M to 0.3268 × 10-2 M.